ANALISIS DETERMINAN DAN DAYA SAING EKSPOR KARET ALAM INDONESIA DI PASAR DUNIA - Raihanisyah Raihanisyah (Fakultas Pertanian, Universitas Riau, 2017)
Natural rubber is one of Indonesia’s leading plantation export with increasing area and production every year. However, Indonesian natural rubber export in the world market has negative growth and even lower growth than a competing country, Thailand. The purpose of this study was to determine the determinant factors of Indonesian natural rubber export value and the competitiveness of Indonesian natural rubber in the world market and compare it with Thailand. Determinant was observed for 10 years (2001-2014) in 10 main Indonesian natural rubber importing countries using Gravity Model theory with natural rubber export value as the dependent variable and GDP per capita of Indonesia and the importing countries, geographic distance, population, real exchange rate, world crude oil price, and IRCo membership as the independent variables. To observe competitiveness, RCA/Revealed Comparative Advantage (comparative advantage) and Vollrath Index (to analyze competitive advantage). The research result showed that the GDP per capita of Indonesia and destination countries, population and IRCo membership had positive and significant influence on Indonesian natural rubber export. Meanwhile, distance, real exchange rate and world crude oil price didn’t significantly influence Indonesian natural rubber export. The result of competitiveness analysis showed that Indonesian natural rubber export had comparative and competitive advantages in the world market. Compared with the main competitor, Thailand, Indonesia was only able to lead in comparative advantage, while Thailand led in competitive advantage.